Development of Discovery Learning-Based Modules for PGSD Students at PGRI Silampari University - Fitriyana, Nur; Purwasi, Lucy Asri (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
This research aims to determine the development of a Discovery Learning-based module for PGSD students that is valid and practical. This research was carried out on first semester PGSD students at PGRI Silampari University. The module development research procedure was adapted from the 4-D learning device development model. Based on the research results, the development of discovery learning-based modules on number sequences and series is in the valid and practical category. This is shown from the results of validation by material, construction/media and language experts who obtained an average score of 0.82, 0.8 and 0.89 respectively with the high validity category. Practicality is shown from the results of observing the implementation of the module, the results of the questionnaire analysis of lecturer and student responses with average scores of 4.7, 4.6 and 4.4 respectively, all in the very practical category.